Optical and electrical properties of ZnO nanoparticle thin films deposited on quartz by sparking process - T. Kumpika (2018)
ZnO nanoparticle thin films were deposited on quartz substrates by a novel sparking deposition which is a simple and cost-effective technique. The sparking off two zinc tips above the substrate was done repeatedly 50-200 times through a high voltage of 10 kV in air at atmospheric pressure. The film deposition rate by sparking process was approximately 1.0 nm/spark. The ZnO thin films were characterized by X-ray diffraction, Raman spectroscopy, UV-vis spectrophotometry, and ionoluminescence at room temperature. The two broad emission peaks centered at 483 nm (green emission) and 650 nm (orange-red emission) were varied after two-step annealing treatments at 400-800 °C. Moreover, the electrical resistivity of the films was likely to be proportional to the peak intensity of the orange-red emission. © 2007 Elsevier B.V. All rights reserved.